2020
DOI: 10.1002/cbic.202000290
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cell Metabolites: Updates on Current Tracing Methods

Abstract: Cancer is the second leading cause of death‐1 in 6 deaths globally is due to cancer. Cancer metabolism is a complex and one of the most actively researched area in cancer biology. Metabolic reprogramming in cancer cells entails activities that involve several enzymes and metabolites to convert nutrient into building blocks that alter energy metabolism to fuel rapid cell division. Metabolic dependencies in cancer generate signature metabolites that have key regulatory roles in tumorigenesis. In this minireview,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 89 publications
(112 reference statements)
0
3
0
Order By: Relevance
“…Para rastrear os diferentes metabólitos correlacionados com diagnósticos e prognósticos de câncer, vários métodos analíticos estão sendo empregados na pesquisa básica e clínica, como espectrometria de massas, cromatografia líquida e gasosa e ressonância magnética nuclear (RMN). Têm sido utilizados isótopos estáveis marcados para rastrear diferentes vias metabólicas, como: PPP, glicólise, CAC e síntese de novo de lipídeos, bem como a análise de perfil metabolômico para identificação de biomarcadores associados ao metabolismo tumoral 44 . Saúde Meio Ambient.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Para rastrear os diferentes metabólitos correlacionados com diagnósticos e prognósticos de câncer, vários métodos analíticos estão sendo empregados na pesquisa básica e clínica, como espectrometria de massas, cromatografia líquida e gasosa e ressonância magnética nuclear (RMN). Têm sido utilizados isótopos estáveis marcados para rastrear diferentes vias metabólicas, como: PPP, glicólise, CAC e síntese de novo de lipídeos, bem como a análise de perfil metabolômico para identificação de biomarcadores associados ao metabolismo tumoral 44 . Saúde Meio Ambient.…”
Section: Discussionunclassified
“…Um grande exemplo com relevância clínica é a FDG-PET (tomografia por emissão de pósitrons com fluorodeoxiglicose), a qual usa um análogo da glicose radiomarcada, para observar captação de glicose e glicólise nos diferentes tecidos do organismo, via imageamento. Assim, o PET-scan permite desde a verificação de presença de tumores e seu estadiamento, até o acompanhamento das respostas terapêuticas do paciente 44 . A literatura já aborda também o imageamento por PETscan usando lactato 17 e glutamina 44 radiomarcados, o que parece ser promissor, visto que estas moléculas acabam sendo utilizadas como combustíveis alternativos para o metabolismo energético de tumores 44 .…”
Section: Discussionunclassified
“…3 Top: mass spectra of the sodiated rifamycin dimer after absorption of one soft X-ray photon; bottom: zoom of the mass spectrum at 100 eV photon energy in the m/z range where peaks assigned to rifamycin monomers as well as loss of neutral molecules are observed assign it to C 1 +Na. 1 Since Na is initially bound to the naphthofuran group in sodiated rifamycin, it indicates that sodium has been transferred to the other side of the molecule. Unlike proton transfer, gas-phase sodium transfer after ionization of molecular systems has not been reported yet, to the best of our knowledge.…”
Section: X-ray Photoabsorption Of the Sodiated Rifamycin Dimermentioning
confidence: 99%
“…Unlike proton transfer, gas-phase sodium transfer after ionization of molecular systems has not been reported yet, to the best of our knowledge. However, previous mass spectrometric studies involving sodium transfer do exist: for instance, Liang et al [31] have observed sodium transfer from doubly sodiated glycerophosphocholine lipids to azobenzene radical anions in the gas phase, Blagojevic and Bohme 1 As stated in the experimental section, to spot background peaks for each photon energy, we record a mass spectrum with the photon beam on and the ESI off, and another mass spectrum with the beam off and the ESI on. We did not find any signal at m/z 416 in any of these spectra.…”
Section: X-ray Photoabsorption Of the Sodiated Rifamycin Dimermentioning
confidence: 99%
See 1 more Smart Citation